Case Report: An association of left ventricular outflow tract obstruction with 5p deletions - Mascho, Kira; Yatsenko, Svetlana A.; Lo, Cecilia W.; Xu, Xinxiu; Johnson, Jennifer; Helvaty, Lindsey R.; Burns Wechsler, Stephanie; Murali, Chaya N.; Lalani, Seema R.; Garg, Vidu; Hodge, Jennelle C.; McBride, Kim L.; et al. (Frontiers in Genetics, 2024)
Introduction: 5p deletion syndrome, also called Cri-du-chat syndrome 5p is a rare genetic syndrome with reports up to 36% of patients are associated with congenital heart defects. We investigated the association between left outflow tract obstruction and Cri-du-chat syndrome.Methods: A retrospective review of the abnormal microarray cases with congenital heart defects in Children's Hospital of Pittsburgh and the Cytogenomics of Cardiovascular Malformations Consortium.Results: A retrospective review at nine pediatric centers identified 4 patients with 5p deletions and left outflow tract obstruction (LVOTO). Three of these patients had additional copy number variants. We present data suggesting an association of LVOTO with 5p deletion with high mortality in the presence of additional copy number variants.Conclusion: A rare combination of 5p deletion and left ventricular outflow obstruction was observed in the registry of copy number variants and congenital heart defects.